2007
DOI: 10.2478/s11532-007-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of unmodified and partially silylated nanosilica with red blood cells

Abstract: Abstract:Interaction of red blood cells (RBCs) with unmodified and partially (50%) silylated fumed silica A-300 (nanosilica) was studied by microscopic, XRD and thermally stimulated depolarisation current (TSDC) methods. Nanosilica at a low concentration C A−300 < 0.01 wt.% in buffered aqueous suspension is characterised by a weak haemolytic effect on RBCs. However, at C A−300 = 1 wt% all RBCs transform into shadow corpuscles because of 100% haemolysis. Partial (one-half) hydrophobization of nanosilica leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Other chemical treatments severely affecting the surface and consequently depressing the hemolytic activity have been ascribed to the involvement of silanols: adsorption of polymers (e.g., poly(2vinylpyridine-N-oxide) (PVPNO)), 10,29 proteins, and lipids (e.g., albumin, lecithin, serum, plasma and corona), 29−31 chloroquine, 32,33 and aluminum compounds (e.g., AlCl 3 , aluminosilicate compounds, and aluminum lactate). 10,16,34 A decrease in hemolytic activity was also observed by replacing the hydroxyl groups with trimethylsilyl groups 35 and by etching silica particles with hydrofluoric acid. 36,37 Recent studies on the porous structure of amorphous silica NPs revealed that mesoporosity for particles of similar size reduced their hemolytic activity because of the depletion of surface silanol groups accessible to the RBC membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other chemical treatments severely affecting the surface and consequently depressing the hemolytic activity have been ascribed to the involvement of silanols: adsorption of polymers (e.g., poly(2vinylpyridine-N-oxide) (PVPNO)), 10,29 proteins, and lipids (e.g., albumin, lecithin, serum, plasma and corona), 29−31 chloroquine, 32,33 and aluminum compounds (e.g., AlCl 3 , aluminosilicate compounds, and aluminum lactate). 10,16,34 A decrease in hemolytic activity was also observed by replacing the hydroxyl groups with trimethylsilyl groups 35 and by etching silica particles with hydrofluoric acid. 36,37 Recent studies on the porous structure of amorphous silica NPs revealed that mesoporosity for particles of similar size reduced their hemolytic activity because of the depletion of surface silanol groups accessible to the RBC membranes.…”
Section: Introductionmentioning
confidence: 99%
“…reported a correlation between the concentration of free surface -SiOH groups and the hemolytic activity, while Murashov and co-workers claimed the density of the geminal silanol groups (two −OH groups linked to the same silicon atom), a minor feature of the silica surfaces, to be responsible for hemolysis. Other chemical treatments severely affecting the surface and consequently depressing the hemolytic activity have been ascribed to the involvement of silanols: adsorption of polymers (e.g., poly(2-vinylpyridine- N -oxide) (PVPNO)), , proteins, and lipids (e.g., albumin, lecithin, serum, plasma and corona), chloroquine, , and aluminum compounds (e.g., AlCl 3 , aluminosilicate compounds, and aluminum lactate). ,, A decrease in hemolytic activity was also observed by replacing the hydroxyl groups with trimethylsilyl groups and by etching silica particles with hydrofluoric acid. , Recent studies on the porous structure of amorphous silica NPs revealed that mesoporosity for particles of similar size reduced their hemolytic activity because of the depletion of surface silanol groups accessible to the RBC membranes. In addition, particle size appears to be related to hemolytic activity for both micro and nanosilicas. Considering micrometric-sized particles, the smaller quartz particles were found to be more membranolytic than the larger ones. , In contrast, hemolytic activity increased with increasing particle size with fumed silica, mesoporous silica, and colloidal amorphous silica NPs .…”
Section: Introductionmentioning
confidence: 99%
“…Scheme of RBC transformation from a discocyte to a shadow corpuscle on interaction with nanosilica: discocyte (1), echinocyte I-IV (2-5), spherocyte (6), and shadow corpuscle (7-8) shown with consideration for their relative sizes(Gun'ko et al 2007) …”
mentioning
confidence: 99%
“…Furthermore, the haemolytic activity of SiO 2 is reduced when OH groups are masked by polymers (e.g., poly(2-vinylpyridine-N-oxide) (PVPNO)) [41], proteins and lipids (e.g., albumin, lecithin, serum, plasma and corona) [101,102], and positively charged molecules, such as chloroquine [103] and aluminium compounds [41]. A decrease in haemolytic activity was also observed when replacing the OH groups with organosilane coatings on both crystalline and amorphous silica (nano)particles [34,104]. All these results supported the idea that the haemolytic activity of SiO 2 particles depends on accessible silanol groups at their surface.…”
Section: Figure 12mentioning
confidence: 99%